Analisis Pengaruh Pertumbuhan Ekonomi, Investasi, dan Belanja Daerah terhadap Ketimpangan Pembangunan Wilayah Provinsi Bali Tahun 2015-2022 - Handayani, Devi Vera; Endang, Endang (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the influence of economic growth, investment and regional spending on regional development inequality in Bali Province in the 2015-2022 period. Using the Common Effect Model (CEM) with panel data. The results of this research show that economic growth, investment and regional spending do not have a significant effect on development inequality that occurs in Bali Province during the 2015-2022 period.